Venous Air Embolism (VAE) during Craniotomy of Supratentorial Meningioma in Supine Position - Sutawan, Ida Bagus Krisna Jaya; Bisri, Tatang; Rahardjo, Sri; Lalenoh, Diana (Bali Journal of Anesthesiology, 2017)
AbstractVenous Air Embolism (VAE) is one of the most serious complications in neuroanesthesia case. The highest number of VAE incident is during neurosurgery procedure with sitting position, even tough VAE may occur during craniotomy of supratentorial tumor in the supine position. VAE occurs due to the pressure differential between open vein in the surgical field and right atrium. A 46 years old woman underwent craniotomy for supratentorial meningioma in the supine position. Intraoperative, the patient was experiencing a decrease in end-tidal CO2 pressure about 6 mmHg in 5 minutes. Therefore, management of acute VAE was proceed to the patient, such as informed the surgeon immediately, discontinued N2O and increased flow of O2, modified the anesthesia technique, asked the surgeon to irrigate the surgical field with fluids, gave compression on jugular vein, aspirated the right atrial catheter, prepared drugs to support the hemodynamic, and changed the patientâs position if possible.Â